Older Adults and Immune Thrombocytopenia: Considerations for the Clinician - Crickx E; Mahévas M; Michel M; Godeau B (Clinical Interventions in Aging, 2023)
Etienne Crickx,1,2 Matthieu Mahévas,1,3,4 Marc Michel,1 Bertrand Godeau1 1Service de Médecine Interne, Centre national de référence des cytopénies auto-immunes de l’adulte, Hôpital Henri Mondor, Fédération Hospitalo-Universitaire TRUE InnovaTive theRapy for immUne disordErs, Assistance Publique Hôpitaux de Paris (AP-HP), Université Paris Est Créteil, Créteil, France; 2Université de Paris, Imagine Institute, Laboratory of Immunogenetics of Pediatric Autoimmune Diseases, Paris, F-75015, France; 3Institut Necker Enfants Malades (INEM), INSERM U1151/CNRS UMS 8253, ATIP-Avenir Team AI2B, Université de Paris, Université Paris-Est-Créteil, Paris, France; 4INSERM U955, équipe 2, Université Paris-Est Créteil (UPEC), Créteil, FranceCorrespondence: Bertrand Godeau, Service de Médecine Interne, Hôpital Henri Mondor, Assistance Publique Hôpitaux de Paris (AP-HP), 51 avenue du maréchal de Lattre de Tassigny, Créteil, 94000, France, Tel +331 49 81 29 05, Fax +331 49 81 29 02, Email bertrand.godeau@aphp.frAbstract: Many epidemiological studies have shown that the incidence of immune thrombocytopenia (ITP) increases after age 60 years and peaks in patients over age 80 years. Therefore, ITP is a concern for physicians taking care of older patients, especially regarding its diagnosis and management. The diagnostic work-up should exclude other causes of thrombocytopenia and secondary ITP, including myelodysplastic syndrome and drug-induced ITP. The treatment decision is influenced by an increased risk of bleeding, infectious diseases and thrombosis in this population and should take into account comorbidities and concomitant medications such as anticoagulant drugs. First-line treatment is based on short corticosteroids courses and intravenous immunoglobulin, which should be reserved for patients with more severe bleeding complications, with their higher risk of toxic effects as compared with younger patients. Second-line treatment should be tailored to the patient’s history, comorbidities and preferences. Preferred second-line treatments are thrombopoietin receptor agonists for most groups and guidelines given their good efficacy/tolerance ratio, but the thrombotic risk is increased in older people. Other second-line options that can be good alternatives depending on the clinical context include rituximab, dapsone, fostamatinib or immunosuppressive drugs. Splenectomy is less often performed but remains an option for fit patients with chronic refractory disease. Emerging treatments such as Syk or Bruton tyrosine kinase inhibitors and FcRn antagonists are becoming available for ITP and may modify the treatment algorithm in the near future. The aim of this review is to describe the particularities of the diagnosis and treatment of ITP in older people, including the response and tolerance to the currently available drugs. We also discuss some situations related to co-morbidities that can frequently lead to adapt the management strategy in older patients.Keywords: immune thrombocytopenia, ITP, elderly, intravenous immunoglobulin, IVIg, thrombopoietin receptor agonists, splenectomy, rituximab